Association of dietary patterns with depressive symptoms in Chinese adolescents: a cross-sectional study - Qian, Kongjia; Wang, Dan; Sun, Yongfang; Ye, Xian; Wang, Dan; Xu, Hongzhen (Frontiers in Nutrition, 2023)
Objective: Depression is highly prevalent in adolescents and may have adverse social and health consequences. To investigate the effect of diet on the occurrence of depression in adolescents, this study examined the correlation between dietary patterns and depression in adolescents. Methods: A total of 853 participants were recruited in October 2022 in Taizhou, Zhejiang, China. The Chinese version of the Patient Health Questionnaire-9 was used to assess the subjects' depressive symptoms in the past two weeks. Relevant dietary information was obtained through a food frequency questionnaire. The associations between dietary patterns and the risk of depression were assessed using a logistic regression model. Results: Four dietary patterns were identified by principal component analysis, including the modern pattern, the snack-aquatic pattern, the traditional pattern, and the vegetarian pattern. The risk of mild depression among adolescents was higher in the Q2 and Q3 groups of the modern model than in the Q1 group of this type, and the risk of mild depression was higher in the Q4 group of the snack-aquatic model than in the Q1 group of this type; while the risk of moderate depressive symptoms was lower in the Q3 group of the vegetarian model compared with the Q1 group. Conclusions: Modern and snack-aquatic patterns are associated with an increased risk of depression in Chinese adolescents, and vegetarian patterns are associated with a reduced risk of depression. The current findings emphasize the importance of adolescents consuming moderate amounts of rice flour, adequate vegetables and fruits, and reducing snack intake.